2006
DOI: 10.1111/j.1365-2249.2006.03199.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces expression of connective tissue growth factor in scleroderma skin fibroblasts

Abstract: SummaryConnective tissue growth factor (CTGF) plays a role in the fibrotic process of systemic sclerosis (SSc). Because hypoxia is associated with fibrosis in several profibrogenic conditions, we investigated whether CTGF expression in SSc fibroblasts is regulated by hypoxia. Dermal fibroblasts from patients with SSc and healthy controls were cultured in the presence of hypoxia or cobalt chloride (CoCl2), a chemical inducer of hypoxia-inducible factor (HIF)-1a. Expression of CTGF was evaluated by Northern and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 53 publications
7
55
0
1
Order By: Relevance
“…38 Hypoxia-inducible factor 1 that is activated on bacterial infection 39 induces CTGF expression, possibly via a hypoxia-responsive element in the CTGF promotor. 40 Peptidoglycan from S aureus causes rapid release of tumor necrosis factor (TNF)-␣ and other inflammatory cytokines resulting in TGF-␤ induction. 41 Similarly, S aureus protein A, a highly expressed surface component, can mimic TNF-␣ to activate its receptor and initiate subsequent proinflammatory 42 and profibrotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…38 Hypoxia-inducible factor 1 that is activated on bacterial infection 39 induces CTGF expression, possibly via a hypoxia-responsive element in the CTGF promotor. 40 Peptidoglycan from S aureus causes rapid release of tumor necrosis factor (TNF)-␣ and other inflammatory cytokines resulting in TGF-␤ induction. 41 Similarly, S aureus protein A, a highly expressed surface component, can mimic TNF-␣ to activate its receptor and initiate subsequent proinflammatory 42 and profibrotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…How hypoxia and ischemia may incite fibrosis is not established. In vitro studies have demonstrated profibrotic phenotypic change of fibroblasts in response to hypoxia (34)(35)(36). Epithelial and endothelial cells can undergo mesenchymal transition under ischemia to become another source of activated fibroblasts (37).…”
Section: Figurementioning
confidence: 99%
“…97 Furthermore, local hypoxia may upregulate PAI-1 expression 103 in the remodeling/organization regions within the thrombi and induce expression of connective-tissue growth factor (CTGF) via a hypoxia-responsive element in the CTGF promoter. 104 Recent data have shown that genetic ablation of the BMPR2 gene in pulmonary endothelium induces in situ thrombosis, suggesting a role for the TGF-β pathway in thrombus organization. 105 …”
Section: Vascular Remodeling In Pementioning
confidence: 99%